Um programa de ensino bilíngüe culturalmente relevante para o Karajá - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1989)
The author discusses linguistic and ethnological research as vital factors in developing the Karajá bilingual teaching program on Bananal Island, in Goiás, now Tocantins. The chiefs of each village selected Karajá interns to become teachers according to their cultural norms. Their training took place in four of the main villages, while the bilingual system was implemented in the schools at the same time. They studied the theoretical aspects and, through their own intuitive teaching patterns, applied them in daily classes. The local community participated in decision-making regarding school matters.
A culturally relevant bilingual education program for the Karajá
Keywords: Etnociência; Literatura karajá; Monitor bilíngüe; Preservação cultural; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA